The State of Political Studies in Interdisciplinary Political Studies 2017-2024: A Bibliometric Analysis - Larasati, Yuniar Galuh; Henky Fernando; Morin, Leanne (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
Abstract This study presents a bibliometric analysis of political research published in Interdisciplinary Political Studies from 2017 to 2024, as indexed by Scopus. Using VOSviewer software, it maps key themes, research trends, and scholarly clusters within the journal's publications. The findings highlight the journal’s contributions to the broader field of political studies while identifying gaps in its coverage of contemporary issues. Notably, the study observes a limited focus on evolving citizen political attitudes and preferences in the context of new media. By providing a baseline assessment, this study enables Interdisciplinary Political Studies to strategically address these gaps, strengthening its position as a leading platform for innovative and impactful political research, particularly in response to the challenges and opportunities of the digital age.